57 Carnosine prevents oxidative damage in myoblast cells derived from porcine skeletal muscle. (5th December 2019) - Palin, Marie-France; Lapointe, Jérôme; Gariépy, Claude; Beaudry, Danièle; Kalbe, Claudia
Abstract: Carnosine (β-alanyl-L-histidine) is a molecule naturally and exclusively present in muscle food with the highest concentrations found in skeletal muscles and brain of the animal. Among its numerous biochemical properties, carnosine has antioxidant activity which include metal ion chelation and free radical scavenging. We have recently reported that high muscle carnosine content in pig is associated with better meat quality. Moreover, supplementing pigs with β-alanine reduced oxidative damage to Longissimus muscle (LM) lipids and proteins. Among previously reported antioxidant activities, carnosine was found to limit the production of reactive oxygen species (ROS) and increase antioxidant enzyme activities. However, these studies were mainly conducted in rodents and cell lines and mechanisms in play remain to be characterized. To determine the effect of carnosine in preventing oxidative damage and characterize the mechanisms in play, we have undertaken experiments using the progeny (myoblasts) of satellite cells isolated from the LM of newborn piglets. Cells were treated with carnosine (0, 10, 25 and 50 mM) for 48 h and were then either collected immediately or treated with H2 O2 (0.3 mM, 1 h) to induce an oxidative stress. Our results showed that carnosine prevents oxidative stress through the reduction of total intracellular ROS and by modulating the antioxidant system in myoblasts.Carnosine increased the mRNA abundance of NEF2L2, a transcription factor activated by oxidative stress, and several of its downstream regulated antioxidant genes. Western blot analyses further suggest that the protective effect of carnosine on H2 O2 -induced oxidative stress is mediated through the p38 MAPK intracellular pathway. Finally, the addition of carnosine to H2 O2 -treated myoblasts increased the basal cellular oxygen consumption rate (OCR), the ATP-linked OCR and proton leaks, thus suggesting an effect of carnosine on mitochondrial functions. Taken together, these findings demonstrate the important role of carnosine in preventing oxidative damage in porcine muscle cells.